Academic Stress Scale untuk Mengukur Tingkat Stres Akademik Mahasiswa Kesehatan Masyarakat Universitas Muhammadiyah Surakarta - Sheena Ramadhia Asmara Dhani; Anisa Catur Wijayanti; Munifatu Rodiyah (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2025)
Academic stress is a common problem among university students, especially in health-related programs where academic demands are complex. Multiple internal and external factors, such as workload, organizational involvement, and financial responsibilities, can increase psychological pressure. Prolonged stress may reduce concentration, academic performance, and overall well-being. This study aims to describe the level of academic stress among Public Health students at Universitas Muhammadiyah Surakarta and examine its variation across individual characteristics. A descriptive quantitative design with a cross-sectional approach was employed, involving 296 respondents recruited through purposive sampling. Data were collected using the Lakaev Academic Stress Response Scale (LASRS), which assesses four dimensions: affective, behavioral, cognitive, and physiological. Analysis included descriptive statistics and cross-tabulation based on gender, organizational activity, employment status, and economic contribution to the family. Results revealed an almost equal distribution of stress levels: low (34.1%), moderate (33.1%), and high (32.8%). Female students, working students, and those supporting family income were more likely to experience higher stress. These findings confirm that academic stress is an unavoidable phenomenon but can function as distress or eustress depending on coping strategies. Therefore, universities should strengthen counseling services, stress management programs, and financial support to promote students' psychological resilience and academic success.